Ethnography Research: Dayak Kaharingan Ethics Kalimantan - Daito, Apollo (Journal of Law, Politic and Humanities, 2023)
This research is an ethnographic on the Kaharingan Dayak in Central Kalimantan, East Barito, and South Kalimantan in Tabalong District, and Gunung Meratus Dayak. The studies were conducted in 2012, 2016, 2018 and 2023. The research units were the male and female Wadian Kaharingan, and the Mantir Adat Dayak. The results of this ethnographic research produced 3 main findings, namely the Dara Mula Lapeh Ethics of Concern, Datu Mula Munta's Environmental Ethics, and the third is the Ethics of Living Together on the Land. The Caring Ethics develops the notion of caring as a feminine ethic, and applies it to the practice of moral education. Women "enter the practical realm of moral action in a different way". The Caring Ethic as a preference for moral deliberation takes place in practice, and an appreciation for the uniqueness of each caring relationship. The ethics of caring as the basis of human existence and awareness. Environmental Ethics is given a holistic intrinsic value, namely including non-human entities, more precisely animals, plants, water, mountains, seas and other organisms in a group of entities that have intrinsic value that must be protected and respected. All biotic and abiotic beings deserve moral judgment for themselves. In other words, along with the human species, all other living things have intrinsic value. Meanwhile, the Ethics of the Dayak Kaharingan are the Ethics of Living Together on the Ground. The results of ethnographic research state that the mental doctrine of the Dayak Kaharingan is mechanical solidarity occurring when society consists of individuals who are different from each other, and social cohesion is obtained to shared values, beliefs, and rituals as a form of collective awareness as well as reducing individuals